Effects of the Facilitative-Peer-Mentoring in undergraduate clinical teaching: preliminary results - Mizhanim Mohamad Shahimin,; Norlaili Arif,; Shaz’ Ain Razak, (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2020)
We presented preliminary results on the effects of the Facilitative-Peer-Mentoring (FPM) in Optometry’s undergraduate clinical teaching via cognitive and psychomotor domains and evaluating acceptance among students. All Year Three Optometry undergraduates were randomly divided into two groups. Each group served as a control group when they are not involved in the FPM activity. The FPM activity was performed by the Year Four students (peer leaders). The peer learner groups’ cognitive and psychomotor improvements and acceptance towards the FPM were evaluated using the Objective Structured Clinical Examination (OSCE), the Objective Structured Practical Examination (OSPE), and the Clinical Teaching Preference Questionnaire (CTPQ). The cognitive domain tested using the OSCE showed a significant difference between the FPM and control groups in both sessions (p<0.05). However, the psychomotor domain (OSPE) showed a significant difference in the first session (FPM group=77.71±7.50 marks; Control group=63.96±13.38 marks; p=0.005), but not in the second session (FPM group=60.83±15.35 marks; Control group=64.17±13.46 marks;p=0.653). Descriptive analysis showed a higher response on the ‘agree’ scale of the CTPQ items 1,4,5,8 and 9. Although the cognitive domain through the OSCE showed no improvement in either session for the groups, the psychomotor domain showed skills proficiency in one of the FPM sessions. The FPM program implemented was widely accepted among the peer learners and was reflected in their positive CTPQ responses. The potential of embedding the FPM in clinical teaching in the core curriculum should be considered to support learning through peers.